Xenophobia, Price Competition and Violence in the Spaza Sector in South Africa - Piper, Laurence; Charman, Andrew (African Human Mobility Review, 2021)
The last decade has seen growing awareness of violent attacks against foreigners in South Africa. This includes attacks against foreign traders in the townships where they are portrayed as ‘taking over’ by out-competing South African traders on price. Central to township trade are neighbourhood grocery or convenience stores colloquially known ‘spaza’ shops. Drawing on evidence from surveys with over 1000 spaza shopkeepers from South Africa’s three main cities, this article makes the case that business competitiveness does not correspond simply with being foreign or South African. While Bangladeshi and Somali shops were, on average, cheaper than South African shops, Zimbabwean and Mozambican shops were actually more expensive. Further, there is also no easy correspondence between being foreign or South African and the experience of violent crime. Some nationalities report levels lower than South Africans, and some higher. However, there does seem to be a correlation between reported levels of violent crime and economic competitiveness: the nationalities whose shops are more expensive reported lower levels of violent crime, while those whose shops are cheaper reported higher levels. This suggests that the chance of being violently targeted is less about nationality, and more about whether you keep prices low and (presumably) profits high. However, the reality is more complicated as the nature of the crime experienced by the more successful shopkeepers differs by nationality. Hence, Somali shopkeepers endure much more violent crime than Bangladeshi shopkeepers. Not only do these findings challenge the myth that all foreign spaza shops are more competitive than South African shops, but also the assumption that all foreign shopkeepers experience the same levels and, especially, forms of violence.